The Shared Cultural Experience: A Comparison of Religious Memes Created by The Church of Jesus Christ of Latter-day Saints, Religious Media, and Church Members. Issue 2 (3rd April 2017) - Brubaker, Pamela; Boyle, Kris; Stephan, David
ABSTRACT: Previous research suggests that Internet memes give voice to and unite otherwise silent and scattered social groups, making them popular in the most contemporary forms of practiced religion (Burroughs & Feller, 2015). This article aims to understand how religious institutions are utilizing memes to create a religious cultural experience compared to independent entities catering to the same audience. Researchers conducted a quantitative content analysis of 826 memes published by three distinct, interconnected entities affiliated with The Church of Jesus Christ of Latter-day Saints, including official Church organizations, unofficial Church organizations, and users with ties to the faith. Memes were examined for their content, form, and stance (Shifman, 2013). An analysis revealed that the LDS Church used its memes to present more serious, inspirational content, while users created memes that were more light-hearted and mixed LDS culture with pop culture. However, unofficial sources created more memes promoting LDS beliefs.